Thermophysical properties of cryoprotectants. VII. Electrical conductivity of some cryoprotectants, their aqueous solutions and mixtures - Todrin, Aleksandr F.; Timofeyeva, Elena V. (Problems of Cryobiology and Cryomedicine, 2015)
The paper classifies the reference data on specific electrical conductivity of water, pure cryoprotectants, their aqueous solutions and mixtures. We obtained empirical polynomial equations for calculating the specific electrical conductivity of water and pure cryoprotectants depending on temperature. Empirical polynomial equations were obtained for aqueous solutions and mixtures of cryoprotectants depending on the temperature and constant concentrations or the one and constant temperature. Probl Cryobiol Cryomed 2015; 25(1): 33-44.